Evaluation of Drug Management and Improvement Strategies Using the Hanlon Method in the Pharmacy Installation of Ki Ageng Selo Wirosari General Hospital, Grobogan Regency, Indonesia - Nugroho Wisnu Putro; Rina Herowati; Gunawan Pamudji Widodo (HM Publisher, 2023)
Drug management in the hospital is one of the important hospital management. Its inefficiency can have a negative impact on the hospital, both medically and economically. The purpose of this study was to evaluate drug management at the pharmacy installation of Ki Ageng Selo General Hospital by using efficiency indicators and implementing improvement strategies using the Hanlon method. This study uses a descriptive design for data that is retrospective and concurrent. Data in the form of quantitative and qualitative accompanied by interviews with related parties. All stages of drug management at the Pharmacy Installation of Ki Ageng Selo General Hospital were measured for their level of efficiency using indicators from the Ministry of Health, Permenkes, and WHO, then compared with standards and described based on priority analysis of action plans using the Hanlon method. The results of the study according to the standards were: the suitability of the available drug items with the RS Formulary (92.21%), the frequency of delayed payments (5 times), the percentage of correctness between the drug and the stock card (100%), the level of drug availability (12 months), average time spent serving prescriptions to patients (non-concocted 7.7 minutes, concocted 17 minutes), percentage of prescriptions with generic drugs (84.9%). Stages of drug management that are not in accordance with standards, namely: the percentage of available capital/funds with all the funds needed (202.14%), the percentage of drug procurement funds allocation (20.17%), the percentage of expired drug value (8.1%), the number of drug items per prescription sheet (4.27). Priorities for handling problems are as follows: 1) Monitor drugs for a maximum of 6 months before the ED, 2) Increase the role of KFT in evaluating and coordinating with doctors regarding the use of drugs to avoid polypharmacy, 3) Evaluation is needed every 3 months or 6 months for budget revisions, 4) carry out an evaluation at the end of each year to determine the budget and better coordination between drug managers and hospital fund providers.